Abelacimab: A leap forward in anticoagulation with FXI and FXIa Inhibition - Hisham A. Badreldin; Nada Alsuhebany; Mohammed Alzahrani; Abdulmajeed M. Alshehri; Maha Aldoughaim; Saleh Alqifari; Omar Yassin; Lama Alfehaid; Tariq Alqahtani (Elsevier, 2024)
Direct Oral Anticoagulants (DOACs) have revolutionized the treatment of thromboembolic disorders, offering targeted, effective, and safer alternatives to traditional anticoagulants like heparins and vitamin K antagonists (VKAs). Despite their benefits, DOACs have drawbacks, including an increased risk of gastrointestinal bleeding and unsuitability for patients with mechanical heart valves. Recent research has highlighted Factor XI (FXI) as a promising anticoagulation target due to its significant role in pathological thrombosis and minor involvement in normal hemostasis. Abelacimab, an antibody that inhibits FXI, has shown potential in transforming anticoagulation therapy by sparing hemostasis. This review provides a comprehensive analysis of abelacimab, examining its clinical pharmacology and its pharmacokinetic and pharmacodynamic properties. It scrutinizes abelacimab's safety profile and key monitoring parameters. The current evidence supporting its use and potential future research strengthening its position in anticoagulant therapy is also discussed. The objective is to enhance understanding and contribute to discussions around developing safer anticoagulants, particularly for patients at risk for thrombosis.